2002
DOI: 10.1159/000051360
|View full text |Cite
|
Sign up to set email alerts
|

Types of Stress within Child Alopecia

Abstract: Background: At the beginning of every dermatopathy, including alopecia areata, one can frequently encounter the presence of a stressful event or situation. We have analyzed the factors that seem to have conditioned the onset of alopecia areata in 180 patients between 5 and 16 years of age. Patients and Methods: In order to elucidate whether or not stress is a cofactor for the development of this dermatological disease, we evaluated the psychosocial reality of the patients and particularly the possible presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The mean prevalence of depressive disorders was 9% (95% CI, 6%-12%) (Figure 2 [16][17][18][19][21][22][23][24][25]51,52 ), with a wide heterogeneity in results (I 2 = 97.4%). Prevalence varied according to the assessment tool used: 20% (95% CI, 9%-31%) for interviewbased studies and 4% (95% CI, 1%-6%) for studies using medical records (Table ).…”
Section: Depressive Disordersmentioning
confidence: 99%
“…The mean prevalence of depressive disorders was 9% (95% CI, 6%-12%) (Figure 2 [16][17][18][19][21][22][23][24][25]51,52 ), with a wide heterogeneity in results (I 2 = 97.4%). Prevalence varied according to the assessment tool used: 20% (95% CI, 9%-31%) for interviewbased studies and 4% (95% CI, 1%-6%) for studies using medical records (Table ).…”
Section: Depressive Disordersmentioning
confidence: 99%
“…A small number of studies related to the pediatric cases have shown the presence of stressful life events before the onset of AA as a potential trigger of the disease at a rate of 9.5% to 81%. [31][32][33][34] In studies conducted with children with vitiligo, a history of stressful life events before the onset of the disease was reported at the rates of 48.8% 15 and 77%. 17 In our study, 61% of children with AA and 86.2% of children with vitiligo had a history of stressful life events in the year prior to the onset of the disease.…”
Section: Ta B L Ementioning
confidence: 99%
“…In the few studies regarding children, stress was described as a potential trigger factor in alopecia areata starting from 9.5% of cases 1 up to 80% 2 . Liakopolou et al 3 .…”
Section: Number and Types Of Stressful Events In Alopecia Areata Gromentioning
confidence: 99%
“…The study of Andreoli 2 proposed as potential stressful events: separations (from people/pets/habits/things/familiar environment) in 37% of cases, relational problems (family/school/with friends) in 32% of cases, but also the difficulties for the child to fulfil the parents’ expectations (especially in school activity) in 24% of cases.…”
Section: Number and Types Of Stressful Events In Alopecia Areata Gromentioning
confidence: 99%